The Influence of Transactional Leadership Style, Continuance Commitment, and Emotional Support for Employee Retention Intentions Gen Z at the Cirebon Shoe Factory - Jaelani, Novalia Pradita; Herlina, Ratih; Novita, Nita; Nurmalitasari, Keke Shabrina (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2026)
Employee retention intention is a strategic issue for organizations, particularly amid high job mobility among Generation Z employees in the manufacturing sector. This study aims to examine the influence of transactional leadership style, continuance commitment, and emotional support on the retention intention of Generation Z employees working in a shoe factory in Cirebon. This study employed a quantitative explanatory approach. Data were collected through a structured questionnaire from 51 Generation Z employees selected using purposive sampling and analyzed using multiple linear regression with SPSS, supported by validity and reliability tests. The results indicate that simultaneously, transactional leadership style, continuance commitment, and emotional support significantly affect employee retention intention. Partially, transactional leadership style has a positive and significant effect, while continuance commitment and emotional support do not show a significant effect. These findings highlight the importance of leadership practices in improving retention intention among Generation Z employees.